IFPRI strategy for engagement with CAADP 2026-2035: Supporting implementation at regional, sub-regional, and national levels - International Food Policy Research Institute (International Food Policy Research Institute, 2025)
This document outlines a comprehensive strategy for the International Food Policy Research Institute (IFPRI) to support implementation of the Comprehensive Africa Agriculture Development Programme (CAADP) 2026–2035. With its renewed focus on transforming Africa’s agrifood systems, CAADP provides a framework to address criti cal challenges captured in six strategic objectives that cover sustainable food production, agro-industrialization, investment mobilization, food and nutrition security, inclusivity, resilience, and governance. Building on its long history of support to the CAADP process, IFPRI’s engagement with CAADP 2026–2035 will focus on providing evi dence, strengthening policy processes, building capacity, and supporting investment mobilization to accelerate Africa’s agrifood system transformation. This strategy identifies specific entry points and pathways through which IFPRI can contribute to achieving CAADP’s six strategic objectives including: (1) research and knowledge genera tion; (2) technical assistance and policy support; (3) capacity development; (4) investment and financing support; (5) monitoring, evaluation, and learning; and (6) stakeholder engagement and convening. Working closely with other CGIAR centers and leveraging its country and regional offices, expertise, partnerships, and extensive expe rience in Africa, IFPRI aims to play a pivotal key role in enabling CAADP’s vision of agricultural transformation and inclusive growth, contributing to food security, economic development, and resilience across the continent. By working across regional, subregional, and national levels, IFPRI will engage with partners to help translate CAADP 2025’s ambitious goals into tangible outcomes for food security, resilience, and economic growth.